BERSAMA MEMBANGUN: Kisah Sukses Partisipasi Desa dalam Pembangunan Infrastruktur di Watubangga - Rahmat Hidayat; Achmad Lamo Said; Putri Murniati (Halu Oleo University, 2023)
The purpose of this study was to determine community participation in village development in Kukutio Village, Watubangga Sub-district, Kolaka Regency. This research used descriptive qualitative research method with the number of informants as many as 9 people. Data collection techniques are observation, direct interviews, and documentation. The data analysis technique is by using data collection, data reduction, data presentation and conclusion drawing. The results showed that community participation in Kukutio Village, Watubangga Sub-district, Kolaka Regency in development was quite good. Community participation in development planning in the form of thoughts, the community participates in musrembang to explore ideas to be conveyed in the village level musrembang. Community participation in development implementation is in the form of contributions in the form of money, property, labor and skill.